Interrelation of speed-strength abilities and indicators of maximum aerobic power - V.V. Volkov,; R.V. Tambovtseva,; A.B. Miroshnikov, (Theory and Practice of Physical Culture, 2023)
Objective of the study was to evaluate the relationship between the maximum aerobic power demonstrated in tests with different duration of the load and the maximum anaerobic power. Methods and structure of the study. The experiment involved 13 highly qualified professional single combat athletes (9 men, 4 women, age 26.6±6 years, weight 72±11.7 kg, height 176.2±10.5 cm). The study was conducted in the department of functional diagnostics of the clinic "International Center for Health Protection" (Moscow). All tests were performed on a bicycle ergometer Lode Excalibur (Netherlands). The maximum aerobic power was defined as the load that the subject completed at least 3/4 of the duration of the step before giving up work. Results and conclusions. It is shown that the absolute maximum aerobic power depends on the rate of load increase in the step test and significantly correlates with the absolute maximum anaerobic power (r=0.68-0.84). For a reliable relationship between the relative indicators of aerobic and anaerobic power, a step test of a shorter duration may be required.